التدفق النفسى و علاقته بالكفاءة الذاتية في التدريس لدى أساتذة الطور الابتدائي - سالم,روميصاء; عمورية,امال (University of Eloued جامعة الوادي, 2024)
The study aimed to find out the relationship between psychological flow and self-efficacy in teaching among primary school teachers,and it adopted the descriptive, correlational approach in achieving its goals,where the psychological flow measure and the self-efficacy measure were applied to a sample estimated at (35) male and female professors (newly integrated). The study results showed the following: • The is no positive statistically significant correlation between psychological flow and self-efficacy in teaching among primary school teachers. • The are no statistically significant differences in the psychological flow of primaryschool teachers according to gender. • The are no statistically significant differences in self-efficacy in teaching among primary school teachers according to gender. • The are no statistically significant differences in the psychological flow of primaryschool teachers depending on the formative track. • The are statistically significant differences in self-efficacy in teaching among primary school teachers depending on the formative track. • The are no statistically significant differences in the psychological flow of primaryschool teachers depending on academic specialization هدفت الدراسة الحالية إلى معرفة العلاقة بين التدفق النفسي والكفاءة الذاتية في التدريس لدى أساتذة الطور الابتدائي, واعتمدت المنهج الوصفي الإرتباطي في تحقيق أهدافها, حيث طبق مقياس تدفق النفسي ومقياس الكفاءة الذاتية على عينة مقدرة ب (35) أستاذا وأستاذة (المدمجين جدد)، وقد أظهرت النتائج الدراسة ما يلي: • لا توجد علاقة إرتباطية موجبة دالة إحصائيا بين التدفق النفسي والكفاءة الذاتية في التدريس لدى أساتذة طور الابتدائي. • لا توجد فروق ذات دلالة إحصائية في التدفق النفسيلدى أساتذة الطور الابتدائي بالاختلاف الجنس. • لا توجد فروق ذات دلالة إحصائية في الكفاءة الذاتية في تدريس لدى أساتذة الطور الابتدائي بالاختلاف الجنس. • لا توجد فروق ذات دلالة إحصائية في التدفق النفسي لدى أساتذة طور الابتدائي بالاختلاف المسار التكويني. • توجد فروق ذات دلالة إحصائية في الكفاءة الذاتية في التدريس لدى أساتذة طور الابتدائي بالاختلاف المسار التكويني. • لا توجد فروق ذات دلالة إحصائية في التدفق النفسي لدى أساتذة طور الابتدائي بالاختلاف التخصص الدراسي. • لا توجد فروق ذات دلالة إحصائية في الكفاءة الذاتية في التدريس لدى أساتذة طور الابتدائي بالاختلاف التخصص الدراسي.
Keywords: التدفق النفسي; الكفاءة الذاتية; self-efficacy; Psychological flow